Orthographic facilitation of oral vocabulary acquisition in primary school children. Issue 5 (May 2023) - Salins, Andrea; Cupples, Linda; Leigh, Greg; Castles, Anne
Children's oral vocabulary acquisition is an important aspect of language development that plays a crucial role in reading and literacy development and subsequent academic success. Therefore, it is important to identify and implement evidence-based effective strategies of vocabulary instruction for primary school children. Orthographic facilitation refers to the benefit afforded to word learning by incidentally presenting spellings when new words are introduced. This study aimed to replicate the orthographic facilitation effect in primary school (Grades 1–6) children and further assess whether children in different grades benefitted differently from the presence of orthography during spoken word learning. To do this, 91 children from Grades 1 to 6 were taught novel picture–word pairs with or without spellings. Word learning was assessed during and after training using behavioural and eye-tracking data from picture-naming and picture–word-matching (PWM) tasks. Irrespective of grade, all children experienced a significant orthographic facilitation effect during training. The post-training results were more task dependent with all grades showing a significant orthographic facilitation effect on the picture-naming task, and only Grades 1 to 4 showing a facilitation effect on the PWM task. The theoretical and practical implications of these findings are discussed.